Characterization and antimicrobial analysis of chitosan composite biodegradable films with addition of clove essential oils - Nur Laili, Muhammad Lokman (2010)
Synthetic films materials mostly used to preserve foodstuffs. Recently, attention has turned to biodegradable films because of environmental reasons. The development of new biodegradable packaging material films, for example, chitosan film, is needed to find alternatives to petroleum-based plastics. Chitosan has antimicrobial activities against different groups of microorganisms, such as bacteria, fungus, and yeast. In this project, gelatin is used as the biopolymers in producing the biodegradable film. Gelatin is an attractive alternative to synthetic plastic materials made from non-renewable resources that can be a hazard to the environment. Since gelatin and chitosan are hydrophilic biopolymers with good affinity and compatibility, they are expected to form composite films with good properties. The film preparation process consist by hydrating gelatin powder with distilled water for 4 hour and then the samples were heated at 60°C before mixed with chitosan based solution. Then, the solution was poured on a glass plate and left it dried. Lastly, the film was peeled off the glass plate after it completely dried. This work also aimed on the antimicrobial analysis of films against E. coli and B. subtilis. Method used in this analysis is zone inhibition assay where the inhibition zone diameter is measured and also liquid culture test where the OD reading was measured using spectrophotometer. Based on the study, the clove essential oil has its own antimicrobial activity onto the films. Thus, from the results, it can be concluded that the biodegradable film has smoother surface, higher thermal stability and slightly higher melting point which obtain from SEM, FTIR, TGA and DSC. Gelatin has great potential for being an additive for the composite film and the amount of plasticizer added in the composite film helps to enhance the properties of the film.